A Case for Ending Monolithic Apps for Connected Devices - , Rayman Preet Singh; Shen, Chenguang; Phanishayee, Amar; Kansal, Aman; Mahajan, Ratul (HotOS Workshop 2015, 2015)
Applications using connected devices are difficult to develop today because they are constructed as monolithic silos, tightly coupled to sensing devices, and must implement all data sensing and inference logic, even as devices move or are temporarily disconnected. We present Beam, a framework and runtime for distributed inference-driven applications that (i) decouples applications, inference algorithms, and devices, (ii) handles environmental dynamics, and (iii) automatically splits sensing and inference logic across devices while optimizing resource usage. Using Beam, applications only specify "what should be sensed or inferred," without worrying about "how it is sensed or inferred." Beam simplifies application development and maximizes the utility of user-owned devices. It is time to end monolithic apps for connected devices.